Equity Theory: The Impact of Perceived Value, Perceived Price, and Environmental Friendliness on Customer Loyalty in The E-Commerce Company Shopee Indonesia - Harris, Allan; Komariah, Rizka (BISNIS, 2026)
This study aims to determine the influence of perceived value, perceived price, and environmental friendliness on customer loyalty at the e-commerce company Shopee Indonesia, using Equity Theory as the theoretical framework for drawing conclusions. Equity Theory focuses on assessing the fairness perceived by stakeholders and customers; it emphasizes the benefits and effects resulting from product usage and the development of brand loyalty. A quantitative research method was employed, utilizing a sample of 76 respondents gathered via Google Forms. Multiple linear regression analysis was used as the analytical technique. The results indicate that perceived value has a positive and significant effect on customer loyalty at Shopee Indonesia; the higher the perceived value, the more loyal the customer becomes. Perceived price has a negative effect on customer loyalty; the lower the price of goods sold by the company, the more loyal customers are in shopping there. Environmental friendliness was found to have no effect on customer loyalty in this study. The Equity Theory approach suggests that customers tend to compare different e-commerce platforms, seeking fairness specifically, the assurance that they have an equal opportunity to receive benefits from the e-commerce service compared to other customers.